DAMPAK PEMBELAJARAN PENJAS TERHADAP PEMBENTUKAN KARAKTER SISWA SDN 03 MINAS BARAT KELAS 5 - Ariyanto, Ariyanto; Sulastio, Agus; Hidayat, Hirja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is the interest of the subject and the character of the students that are not good. For example there are still many students that underestimate the lesson and do not appreciate the teacher who teaches. The purpose of this research was to determine the impact of physical education learning on the character formation of students at SDN 03 Minas Barat Class 5. The sampling technique was purposive sampling. The instrument used in this research is to use a questionnaire, interviews and documentation. The data obtained were analyzed using the percentage test technique. From the results of the analysis on the interpretation of scores obtained in the calculation of accumulation or total data obtained 18 respondents or 40% of the impact of physical education learning on students' attitudes in the very good category and 14 respondents 31.11% agreeing the impact of physical education learning in the agree category, and agreeing the impact of not agreeing , if it is said then the results of this research get 32 students or 70% agree and have an impact on physical education learning in the very good category. Based on the analysis of this research, the acquisitions of class VA and B students were made in good categories with the following details: 37.50% or as many as 6 respondents were classified as strongly agree, 31.25% or 5 respondents were classified as agree, 12.50% or 2 respondents were classified as disagreeing and 18.75% or 3 respondents classified as strongly disagreeing.Key Words: Physical Education, Character Establishment